抒情作家莫河的地方经验 ： 故土、历史与文化的记忆 = Lyrical writer Mo He's local experiences : the memories of homeland, history and culture - 蒋承耘 Jiang, Chengyun (Nanyang Technological University, 2021)
从1950年开始至2010年左右，新加坡华文作家莫河进行了长达50多年的散文创作，持之以恒的创作精神体现出他对华文文学与华族文化的热忱。莫河对生活充满激情，他的散文极具抒情特色和乡土情怀，被誉为新加坡的“抒情圣手”。莫河笔下之作体现出对民族文化真切的关怀，深刻反思了人文社会。他的创作呈现出新马一代独具风味的南洋色彩和和地质风貌，对推动新马华文文艺，有着一定的贡献。本文旨在研究莫河的散文抒写，通过对莫河多本散文集的整理和阅读，结合适当的文学批评理论进行分析，深入探讨其散文中的抒情艺术与地方经验。莫河的写作特色是具有童真童趣，感情真挚，文字浅白。在整体脉络上，莫河的散文铺展出新马地区的发展进程，具有历史性与空间性。他的地方书写，含有浓郁的乡土气息，呈现出南洋环境的蕉林椰雨和社会文化。在人与环境的关系里，莫河的城市书写表达出对自然世界的精神追求和情感寄托，并赋予地方想象的符号和象征意义。在历史记忆中，莫河对于历史事件省思透辟，他反对殖民主义和帝国主义，抨击战争的残酷，推崇文明、自主的国家。在后殖民语境中，他对社会挑战和文化冲击进行了深刻的审视。莫河作为南洋华人，其国族认同感是值得研究的一点。他表现出对华族文化的认同和对新加坡强烈的归属感，并且试图寻求宗乡传统与国家未来的平衡发展。莫河与地方之间的羁绊，让他时常抒发土地之情，他的散文里包涵了对故乡的亲切感、故土怀旧和离散乡愁。莫河善于对不同地方进行描写，具有对国族文化、战争殖民、社会问题的眷注和思索，展现了新马一带在历史、政治与经济上的嬗变。Mo He, a Singaporean Chinese author, had been publishing Chinese literary works for more than 50 years (1950s to 2010s). His long-spanning writing career was a result of his deep passion in the subject. Mo He was very passionate and his lyrical prose revealed a great appreciation of the rustic village atmosphere of Singapore’s past. Mo He imbued his prose with his deep thoughts and feelings, and he reflected deeply in humanistic and cultural concerns. Mo He’s prose creation presented the uniqueness of Southeast Asia and Nanyang culture, and also contributed to the promotion of Singapore and Malaysia’s art and literature. This thesis aims to discuss Mo He’s writings through (i) examining and compiling Mo He’s multiple prose collections, and (ii) applying the appropriate literacy criticism theories to analyse and discuss the lyricism and local experiences in his prose. Mo He's writing style is simple and pure, filled with sincerity. His prose also shows the development of Singapore and Malaysia in both historical and spatial contexts. His writing contains a strong rustic atmosphere, shows the social culture of the Nanyang environment. Mo He expressed his mental and emotional pursuit towards the natural world and provided symbolic meanings to express his local imagination of the land. Through Mo He’s historical memories, we can see that he opposed the concepts of colonialism and imperialism, and heavily criticised the cruelty of war. As such, he supported decolonisation and an independent governance. He conducted a profound examination of the social challenges and cultural shocks during the post-colonial period in Southeast Asia. In the study of national identity, Mo He being a Nanyang Chinese, showed that he had a strong Chinese cultural identity. He also had a strong sense of belonging to Singapore and he hoped Singapore could strike a balance between its growing nation-state identity and traditional cultural roots. Mo He’s prose always contained themes surrounding diaspora, nostalgia and homesickness. His account of his travels and his living environment was a valuable commentary of the historical, political and economic changes occurring in Singapore and Malaysia.